Relationship between pistol players' psychophysiological state and shot performance: Activation effect of EEG and HRV - Wang, K.; Li, Y.; Liu, H.; Zhang, T.; Luo, J. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Objective To understand the mechanism of dual activation of the brain and heart in pistol athletes during shooting performances, through synchronized monitoring of electroencephalogram (EEG) and electrocardiogram (ECG).